DPPH Free Radical Scavenging Activity of Combined Leaf Extracts of Gynura procumbens (Lour.) Merr. and Psidium guajava L. - Rengganis Ulvia; Devika Nurhasanah; Azhari Byhaqy; Virani Nur Afrida; Mitsalina Arifah (MEDIA ILMU KESEHATAN, 2025)
Background: The formation of free radicals in the body can be prevented by administering antioxidants. The leaves of Gynura procumbens (Lour.) Merr. and Psidium guajava L. individually possess antioxidant activity. The combination of the two plants is expected to produce enhanced antioxidant activity.Objective: This study aimed to determine the DPPH free radical scavenging activity of a combination of Gynura procumbens (Lour.) Merr. and Psidium guajava L. leaf extracts.Method: Sample extraction was performed using Ultrasound Assisted Extraction (UAE) with ethanol (1:10 w/v). Each extract was subjected to phytochemical screening and tested for DPPH free radical scavenging activity using UV-Vis spectrophotometry. An independent SPSS T-test analysis was performed on the antioxidant activity data (IC₅₀ values) with a 95% confidence level.Results: The results of the phytochemical screening test showed that each extract contains alkaloids, flavonoids, phenolics, tannins, and saponins. The DPPH free radical scavenging activity of the standard quercetin produced an IC₅₀ value of 2.231 ppm, and the combination of Gynura procumbens (Lour.) Merr. and Psidium guajava L. leaf extracts (1:1) produced an IC₅₀ value of 19.454 ppm.Conclusion: The combination of Gynura procumbens (Lour.) Merr. and Psidium guajava L. has very strong DPPH free radical scavenging activity.